Taufiq Rafat’s Foothold: Subverting the Grand Narrative of Sufism - Madeeha Dustgir; Muhammad Aziz Raza; Mufeeza Rauf (Dialogue Social Science Review (DSSR), 2025)
The present study aims to explore the renewal in the standards of Sufism that is based on the traditional parameters of historical standards. Sufism is the name given to the mystical movement within Islam. A Sufi is a Muslim who dedicates himself to the quest after mystical union with his Creator. The basic purpose of this research is to connect faith and knowledge with Sufis as a leader. According to Taufiq Rafat no one can follow the traditional standards of Sufism in present era. He wants to say through his play there is need to make a review in the standards of evaluating the Sufi figure and there is need of transformation in the myth of Sufism according to the present condition of Sufism. However, Taufiq Rafat's play Foothold challenges the traditional and established Sufi figure. The play presents phenomena of gaining God's pursuit by creating a balance between the physical and spiritual world. The play creates a new and unconventional kind of Sufi, who is not cut off from the physical world, and faces and searches the solution of his problems. The Play presents a Sufi who leads a normal life and achieves his contentment in being able to spend a life which solves everyday affairs. The major concern of this study to explore the reality behind overall scenario. To find out the truth between actual Sufis and modern and political Sufis or redefine (Saleem seems a political figure more than a sufi character). This research explores the Sufi of Taufiq Rafat exists on a common plane with the ordinary humans rather than an elevated spiritual plane.